The Importance of Developing a Cartogram through Assessment of Land Quality and Quantity in Zangiota District - M. B. Nurmanova (Research Parks Publishing LLC, 2022)
This article is about the development of cartographic methodology of quality and quantity indicators of agricultural lands of Zangiota district and the creation of quantitative and qualitative map schemes of the research area.